HVOF and laser cladded Fe-Cr-B coating in simulated biomass combustion: microstructure and fireside corrosion - Reddy, Liam; Shipway, P.H.; Davis, Colin; Hussain, Tanvir (Springer, 2017)
Biomass is often considered as a low carbon alternative to fossil fuels in the power industry. However the heat exchangers in biomass plants can suffer from chloride based aggressive fireside corrosion. A commercially available amorphous Fe-Cr-B alloy was deposited onto a stainless steel substrate by HVOF thermal spray and laser cladding. The controlled environment corrosion tests were conducted in a HCl rich environment at 700°C for 250 h with and without KCl deposits. The samples were examined with XRD, SEM and EDX mapping to understand the corrosion mechanisms. In the absence of any deposits, the amorphous HVOF coating performed very well with a thin oxide growth whereas the crystalline laser cladding suffered from ~350 μm metal loss. The scales were composed of MnWO₄, Fe₂O₃, Fe₃O₄ and Cr₂O₃. When a KCl deposit was present, the HVOF sprayed coating delaminated from the substrate and MnCl₂ was found in the scale.